From engineering to economics - CHENERY, H. (PSL Quarterly Review, 2013)
The paper is a contribution to a series of recollections and reflections on the professional experiences of distinguished economists which the Banca Nazionale del Lavoro Quarterly Review started in 1979. Hollis Chenery recounts beginning his professional career as a petroleum engineer and moving on to other branches of engineering and meteorology, before eventually going on to teach economics and work on the economic problems of developing countries for the majority of his life. JEL: B31